Utilizing ELSA In Improving Students’ Pronunciation - Donna Ria Pasaribu; Tiara Kristina Pasaribu; Sahat Taruli Siahaan; Ardiwan Halawa; Naomi Suryana Manurung (LPPM Universitas PGRI Sumatera Barat, 2024)
This study analyzed how technology could be used to improve students’ pronunciation skill. The researcher used English Language Speaking Application (ELSA) to help the Pronunciation students in the first semester of the Faculty of Arts and Music in HKBP Nommensen University, Medan, North Sumatra, Indonesia. There were 27 students who participated as subjects in this study. The main problem in teaching pronunciation in a big class where there are very little personal Lecturer-student interaction. Therefore, this study was conducted to investigate students’ pronunciation improvement using ELSA application. The study used the classroom action research (CAR). The study was done in three cycles. The results showed improvement in students’ pronunciation in English. According to the result of the pre-test (cycle 1) the data showed the mean of the pre-test as 57.92 where 81.48% of the students passed the criterion of minimal score. Int the first cycle, there was a 4.7% increase with the mean score of 60.66 and the the number of students who passed criterion of minimum score was 92.59%. In the last cycle, students showed 14.19% increase. There was 100% of students who passed the criterion minimal score.